Book Review: South Pacific Property Law - Angelo, A H (Victoria University of Wellington Law Review, 2005)
This article is a book review of Sue Farran and Don Paterson South Pacific Property Law (Cavendish Publishing, London, 2004) (300 + xli pages) NZ$95. The book is part of a series of books which has been produced by the staff of the Law School of the University of South Pacific. Property law is diverse and continually changing, and there is a paucity of accessible information about the property law in the South Pacific. As the subject matter has broad coverage, and because of the difficulty of access to the law in most Pacific jurisdictions, Angelo notes that the authors will not have specific knowledge of all the laws in the field. However, Angelo ultimately concludes that the book is a treasury of property law material and a full text which will be of value as a point of reference and starting point for research.